JPEG2000 & JPEG : Objective And Subjective Quality Measures For Lossily Compressed Medical Images - Oh , Tick Hui (2003)
Due to the constrained bandwidth and storage capacity , medical images must be compressed before transmission and storage. However , the compression will reduce the image fidelity, especially when the image is compressed at lower bit rate, which cannot be tolerated in medical field. In this thesis, the compression performance of the new JPEG2000 and the more conventional JPEG is studied.